International Perspectives on the Impact of the COVID-19 Pandemic on Adherence to Prescribed Dual Antiplatelet Therapy: A Window Into Acute Cardiovascular Care. Issue 3 (17th June 2022) - Pollack, Charles V.; Steg, P. Gabriel; James, Stefan; Jolly, Sanjit; Kosiborod, Mikhail; Bonaca, Marc P.
Abstract : An international panel of expert clinicians and researchers in acute cardiac care was convened to review, describe, and contextualize their varied experiences delivering care and maintaining ongoing research during the first year of the COVID-19 pandemic and beyond. A proposed perspective from which care and outcomes could be viewed was the possibility that without routine follow-up and as-accustomed interactions with their care team, patients at risk of acute atherothrombotic events might be less adherent to prescribed antiplatelet medications. This might be manifested by more emergency coronary events or by an increased (and perhaps unidentifiable) incidence of out-of-hospital cardiovascular deaths related to patient anxiety about presenting to hospital during the pandemic. The experiences of the panel members were similar in many regards, which identified opportunities for improvement in cardiac care the next time there is a substantial disruption of usual practice. Regardless of geography or payor system, there was an identified need for better remote care platforms; but stronger infrastructure and consumer facility with remote care technology, improved provider-patient communication to help ensure adherence to primary and secondary prevention medications, and longer-term prescription fills and no-hassle refills on such medications. Profound disruptions in acute cardiovascular research highlighted the need for redundancy or back-up planning for teams engaged in time-sensitive research, to ensure both continuity of protocols and patient safety.